The use of platelet-rich plasma injections in the treatment of meniscal injuries - review of the literature - Katarzyna Wiejak; Kinga Przyborowska; Michał Łata; Beata Getka; Justyna Kwiecień; Mateusz Rukat; Agnieszka Strojny (Kazimierz Wielki University, 2024)
Introduction: In the knee joint are two menisci, which are fibrocartilaginous structures. The tears of the meniscus are one of the most common injuries within knee. Arthroscopy with suturing of torn or menisectomy are the most popular methods of treatment, however in long term observation menisectomy often results in osteoarthritis 10-20 years after surgery. For this reason, less invasive treatment methods are being sought, such as platelet-rich plasma injections. Platelet-rich plasma has many growth factors, which stimulates healing. Objective: The aim of this study is to review latest the literature on the use of platelet-rich plasma injections in the patients with meniscus tears. Material and methods: A literature review was conducted on databases such as PubMed and Google Scholar using the terms: "meniscus", "meniscus tear", "platelet-rich plasma", "platelet-rich plasma injections", "meniscus injuries treatment'. Conclusions: The injuries of meniscus are very common, and often must be treated by arthroscopy. Platelet-rich plasma has a positive impact on tissue healing. Platelet-rich plasma injuries in the patients with meniscal tears repair lead to improve healing rates compare with patients without PRP injections, but there is no guidelines and further studies are necessary.